Mapping the Potentials of Monster Studies - Limpár, Ildikó (Hungarian Journal of English and American Studies, 2021)
Book review: Weinstock, Jeffrey Andrew, ed. The Monster Theory Reader. University of Minnesota Press, 2020. ix + 560 pages + 33 b&w photos. ISBN 978-1-5179-0525-5. 35.00. Pbk.